2013
DOI: 10.1021/es402708v
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Novel Polytitanium Tetrachloride Coagulant for Water Purification

Abstract: Polymeric metal coagulants are increasingly being used to improve coagulation efficiency, yet the research on the development of titanium and particularly polytitanium salts remains limited. This study is the first attempt in the synthesis, characterization, and application of polytitanium salts as coagulants. Polytitanium tetrachloride (PTC) solutions with different basicity values B (OH/Ti molar ratio) were prepared using a slow alkaline titration method. Jar tests were conducted to assess coagulation perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 48 publications
0
54
5
Order By: Relevance
“…The floc growth rate was calculated by the slope of the rapid growth region [16]. In this study, the highest floc growth rate was obtained when Al/Fe = 7:1 and B = 1.5, where the most negative zeta potential was found.…”
Section: Floc Growthmentioning
confidence: 69%
See 1 more Smart Citation
“…The floc growth rate was calculated by the slope of the rapid growth region [16]. In this study, the highest floc growth rate was obtained when Al/Fe = 7:1 and B = 1.5, where the most negative zeta potential was found.…”
Section: Floc Growthmentioning
confidence: 69%
“…This behavior is known as reversible breakage, and the flocs are considered to be held by weak inter-particle bonds, such as van der Waals force [15]. However, some researchers have reported some irreversible breakage, which generally occurs when sweep coagulation is the dominant mechanism, and in that case, flocs could not achieve the initial floc size after breakage [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that pre-hydrolysis was able to effectively improve the on sludge conditioning efficiency of TSCs, and moderate pre-hydrolyzed TSC (TSC 0.5 ) was more effective than other TSCs (Ti 4þ and high-polymeric species) in improving sludge dewatering performance. Zhao et al (2013) suggested that degree of polymerization reached the maximum by raising the B value to 1.5, while it would decrease due to decomposition of hydrolyzed products under alkaline conditions. It should be noted that sludge pH was sharply decreased to 2e3 after addition of TiCl 4 , which might affect the subsequent treatment and disposal of sludge, such as composting, land use and incineration.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, little information is known so far about these species. Considering that the pre-hydrolyzed species of several metal ions have been proved to exert positive effect on flocculation (Liu et al, 2008;Zhao et al, 2013), it was speculated whether copper(II) also had similar effect, promoting the flocculation of TC. To verify this hypothesis, ESI-TOF-MS, a rapidly advancing technique (Feng et al, 2015), was employed.…”
Section: Microscopic Properties Of Flocsmentioning
confidence: 99%